2019
DOI: 10.3390/v11020170
|View full text |Cite
|
Sign up to set email alerts
|

The Three Essential Motifs in P0 for Suppression of RNA Silencing Activity of Potato leafroll virus Are Required for Virus Systemic Infection

Abstract: Higher plants exploit posttranscriptional gene silencing as a defense mechanism against virus infection by the RNA degradation system. Plant RNA viruses suppress posttranscriptional gene silencing using their encoded proteins. Three important motifs (F-box-like motif, G139/W140/G141-like motif, and C-terminal conserved region) in P0 of Potato leafroll virus (PLRV) were reported to be essential for suppression of RNA silencing activity. In this study, Agrobacterium-mediated transient experiments were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…At 5 dpi, GFP fluorescence showed that the LP mutant did not affect its VSR activity; however, the LPP mutant abolished its VSR activity ( Figure 3 C). These results were consistent with a previous observation for enamovirus pea enation mosaic virus-1 P0, where substitution of the conserved LP residues did not affect the suppressor activity while substitution of the conserved LPP residues inhibited its suppressor activity [ 55 ]. Western blot analyses showed that GFP protein accumulation was consistent with fluorescence levels ( Figure 3 D).…”
Section: Resultssupporting
confidence: 93%
“…At 5 dpi, GFP fluorescence showed that the LP mutant did not affect its VSR activity; however, the LPP mutant abolished its VSR activity ( Figure 3 C). These results were consistent with a previous observation for enamovirus pea enation mosaic virus-1 P0, where substitution of the conserved LP residues did not affect the suppressor activity while substitution of the conserved LPP residues inhibited its suppressor activity [ 55 ]. Western blot analyses showed that GFP protein accumulation was consistent with fluorescence levels ( Figure 3 D).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the replacement of W140A in the G139/W140/ G141-like motif weakened P0 activity (Zhuo et al, 2014). Recently, Rashid et al (2019) confirmed these findings for a Canadian P0 PL and revealed that the VSR-defective mutants in the F-box-like motif, the G139/W140/G141-like motif, and in the C-terminus of P0 (F220) affected not only virus accumulation but also its systemic movement.…”
mentioning
confidence: 65%
“…With these results, Rashid et al (2019) demonstrated that P0 is required for PLRV accumulation and systemic infection.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Several viral proteins interacting with SKP1 have been identified, including Clinkprotein, which is encoded by the single-stranded DNA nanovirus faba bean necrotic yellows virus (FBNYV), P0 protein encoded by the poleroviruses beet western yellows virus (BWYV), cucurbit aphid-borne yellows virus (CABYV), brassica yellows virus (BrYV), P7-2 encoded by rice black-streaked dwarf virus (RBSDV), and βC1 encoded by cotton leaf curl Multan virus (CLCuMuV) [16,17,18,19,20]. Among these, the silencing suppressor protein P0 of BWYV and CABYV functions as an F-box protein that targets AGO1 for degradation via the autophagy pathway [21,22,23,24,25]. Although several proteins have been reported to interact with SKP1, only the Polerovirus silencing suppressor P0 has the properties of an F-box protein.…”
Section: Introductionmentioning
confidence: 99%